IMPLEMENTASI DAN PENGUJIAN KINERJA ORACLE 10g REAL APLICATION CLUSTER (RAC) PADA SISTEM OPERASI SUN SOLARIS 10 - Gatot Budi Santoso; Yanuar Indra Wirawan (PETIR, 2015)
During the implementation of database system, needs of getting fast, accurate and highavailabilitydata, has become major clauses for the implementation of “high-availability” system.Oracle 10g RAC is a clustered database solution that requires a two or more node hardwareconfiguration capable of working together under a clustered operating system. A clusteredhardware solution is managed by cluster management software, usually provided by the hardwarevendor. The operating system is also responsible for providing access to the shared disksubsystems. Parameters that used for the performance testing and analyzing of Oracle 10g RealApplication Cluster are the cpu idle, free memory, SGA, buffer cache, and shared pool. As result forthe performance testing and analyzing, it can be concluded that Oracle 10g Real ApplicationCluster was really good for the implementation of “high-availability system” concept. But it alldepends to the analysis for its system.